MGIMO-UNIVERSITY 70TH ANNIVERSARY. POLITICAL SCIENCE ACADEMIC SCHOOL AT MGIMO-UNIVERSITY: ESTABLISHMENT AND MAIN STAGES IN DEVELOPMENT - Alexei Voskressenski; Ekaterina Koldunova; Igor Okunev (Сравнительная политика, 2015)
School of Political Affairs of MGIMO-University proves to be the oldest of all Russia’s political science schools, however at the same time it is very young — it celebrated only 15 years in the year of the 70th MGIMO anniversary. In contrast to many other universities, oriented towards training political science lecturers or practical political consultants, MGIMO has formed its own unique, “complete cycle” political science school which is both academic and practical and is expected to teach political scientists starting from the zero level up to the highest level of proficiency as lecturers and researchers, as well as applied analysts, consultants and practicians. The originality of MGIMO political science school allows its organizational analogue, School of Political Affairs, to offer applicants to acquire wide range of requested professions and specializations, concurrently providing them deeper practical as well as theoretical training.